2020
DOI: 10.24200/amecj.v3.i02.99
|View full text |Cite
|
Sign up to set email alerts
|

Separation and determination of mercury from nail and hair in petrochemical workers based on silver carbon nanotubes by microwave-assisted headspace sorbent trap

Abstract: In this work, a robust method was developed for the determination of mercury in nail and hair in petrochemical workers. By experimental procedure, 100 mg of hair and nail of workers was prepared as a powder which dried in the oven for 20 min at 95oC.  20 mg of hair or nail samples added to reagents (HNO3/H2O2; 5:1) in polyethylene tube (PET) of microwave digestion and the mercury in resulting solution was removed with silver nanoparticles pasted on multi-walled carbon nanotubes (Ag-MWCNTs) which were pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Greater production of ROS can lead to oxidative stress and may induce dysfunctions and structural damages such as mutagenesis, carcinogenesis, oxidation, and deterioration of proteins, carbohydrates, lipids and DNA [23]. Numerous studies have also identified a significant positive relationship between the dose of mercury exposure in hair samples and high blood pressure [24]. In the cardiovascular system, the endothelium functioning is essential to the maintenance of the blood flow and the antithrombotic capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Greater production of ROS can lead to oxidative stress and may induce dysfunctions and structural damages such as mutagenesis, carcinogenesis, oxidation, and deterioration of proteins, carbohydrates, lipids and DNA [23]. Numerous studies have also identified a significant positive relationship between the dose of mercury exposure in hair samples and high blood pressure [24]. In the cardiovascular system, the endothelium functioning is essential to the maintenance of the blood flow and the antithrombotic capacity.…”
Section: Introductionmentioning
confidence: 99%